THE FORMATION OF THE CONCEPT OF PSYCHOLOGICAL RESILIENCE AND ITS MODERN SOCIAL-PSYCHOLOGICAL INTERPRETATIONS - Shavkatov , Shaxboz (INTERNATIONAL CONFERENCE ON MODERN RESEARCH AND SCIENTIFIC INNOVATION, 2026)
This article analyzes the evolution of the concept of psychological resilience, its stages of formation, and its modern socio-psychological interpretations. The study emphasizes viewing resilience not merely as an individual trait, but as a dynamic process of interaction with social systems such as family, community, and society. The article provides practical recommendations for enhancing resilience through institutional support and collective interventions, and highlights the strategic importance of “social buffers” in managing contemporary crises.